1970
DOI: 10.13057/biodiv/d060205
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Diversity in Sumba Island

Abstract: Bamboo is one of the economic plant which grow widely in the villages and have been used by the local people in the villages. Indonesia has about 10% of the world bamboo, 50% among them was endemic to Indonesia. According Widjaja (2001) Lesser Sunda Island which consists of Lombok, Sumbawa, Flores, Timor, Sumba and other small island eastern of Flores has 14 bamboo species, however, the information from the Sumba Island was lacking because of lacking data from this area except one species which was proposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…This information was used to produce a distribution map of each species. Observation of morphological characteristics and identification referred to several references in the literature (Widjaja, 1987(Widjaja, , 1997(Widjaja, , 2001aWidjaja and Karsono, 2005). The important characteristics observed for identifying bamboo species were the color of the bamboo shoots; the branching system, the culm sheath (including auricle, blade, bristle and ligule) and the leaf (including auricle, bristle, ligule and leaf blade).…”
Section: Sampling Identification and Observation Of Morphological Cha...mentioning
confidence: 99%
See 1 more Smart Citation
“…This information was used to produce a distribution map of each species. Observation of morphological characteristics and identification referred to several references in the literature (Widjaja, 1987(Widjaja, , 1997(Widjaja, , 2001aWidjaja and Karsono, 2005). The important characteristics observed for identifying bamboo species were the color of the bamboo shoots; the branching system, the culm sheath (including auricle, blade, bristle and ligule) and the leaf (including auricle, bristle, ligule and leaf blade).…”
Section: Sampling Identification and Observation Of Morphological Cha...mentioning
confidence: 99%
“…6A, Gigantochloa was found mostly in residential areas, dry land agriculture and rice fields because it is often cultivated for many benefits (Widjaja, 2019). In addition, the presence of Gigantochloa in bush areas, transmigration areas, water bodies and even mining areas indicated that Gigantochloa is a cultivated bamboo genus that can live in various areas (Widjaja and Karsono, 2005). Response curve to warmest quarter precipitation in Fig.…”
Section: Responses Of Variable To Suitabilitymentioning
confidence: 99%
“…Spesies bambu di dunia diperkirakan ada 1.200 spesies yang tersebar di 70 negara dengan luas tanaman bambu sekitar 22 juta ha (Jasni et al, 2017). Widjaja (2005) menginformasikan bahwa di Indonesia tumbuh 157 jenis bambu yang merupakan lebih dari 10% jenis bambu di dunia. Zaia et al, (2015) melaporkan bahwa penggunaan bambu sembilang sebagai bahan baku papan partikel menggunakan perekat polyurethane menghasilkan sifat mekanis (MOE dan MOR) yang telah memenuhi standar JIS A 5908 (2003) dengan kisaran antara 5,7 GPa dan 14 N/mm 2 .…”
Section: Pendahuluan Iunclassified
“…Wilayah Nusa Tenggara sebenarnya juga menjadi kegiatan eksplorasi (Widjaja & Karsono, 2005)-namun karena kondisi wilayah berupa kepulauan yang menyebabkan kegiatan eksplorasi tidak maksimal menyebabkan banyak keanekaragaman hayati di wilayah Nusa Tenggara masih belum terungkap. Terbukti ketika dilaksanakan eksplorasi keanekaragaman hayati di wilayah Sumba Timur pada tahun 2016, Damayanto & Widjaja (2016) hanya memperoleh satu jenis bambu; dan Widjaja & Karsono (2005) juga telah melakukan eksplorasi bambu di wilayah Pulau Sumba namun hanya menemukan jenis bambu yang sama. Widjaja, dkk (2014) mengatakan hampir seluruh wilayah Indonesia telah dilakukan pengumpulan koleksi flora, hanya saja belum dilakukan eksplorasi pada sebagian daerah di Indonesia, khususnya bambu yang ada di pulau-pulau kecil di Indonesia.…”
Section: Lokasi Koleksi Spesimen Tipe Bambu Bounclassified